Rapid monitoring of species abundance for biodiversity conservation: Consistency and reliability of the MacKinnon lists technique - MacLeod, Ross; Herzog, Sebastian K.; Maccormick, Aidan; Ewing, Steven R.; Bryce, Rosalind; Evans, Karl L. (Biological conservation, 2011)
Effective monitoring of biodiversity for conservation requires information on spatial and temporal variation in species’ abundances. As conservation resources are limited, monitoring methods are required that enable rapid and cost effective data collection. There are many traditional methods of estimating absolute abundance, such as territory mapping and distance sampling. However, these typically require more time, expertise and finances than are available across much of the globe. This is especially so in the tropics, where high species richness, low densities of many species and structurally complex environments also make monitoring particularly challenging. The MacKinnon lists technique is a rapid assessment methodology designed for use in species rich environments. This method is typically used to estimate species richness, but it has also been suggested that it can generate consistent abundance indices, even when observer experience and environmental conditions vary. If this suggestion is correct, the MacKinnon lists method could be used to assess spatial or temporal changes in abundance using diverse survey data. Here, we provide the first detailed assessment of intra- and inter-observer consistency of the Mackinnon List method in generating species abundance indices that could be useful for conservation monitoring purposes. As a case study, we use one of the world’s most diverse avifaunas, that of the forested Bolivian Andes. We show that MacKinnon lists can provide species abundance indices that are consistent between observers of markedly different experience of the focal avifauna (zero to six years), and between assessments carried out in different stages of the breeding season, between which detectability of individuals differed significantly. We believe this is the first time that a biodiversity monitoring method has been demonstrated to produce consistent abundance indices for a highly diverse avian tropical assemblage. We also suggest that the MacKinnon lists methodology has the potential to be a very useful conservation monitoring tool for many taxa in species rich environments, such as the tropics.